DISTRIBUTION AND LIFESTYLE OF LEUCOZONELLA MESOLEUCA - Zafar M. Makhmudjonov; Seitveli S. Abdurashitov; Bahrom E. Chutanov (EPRA International Journal of Research and Development (IJRD), 2022)
The article studies the spread of Leucozonella mesoleuca and its life under natural conditions. Leucozonella mesoleuca enters to the Hygromidae family’s Leucozonella generation, and this type is separate from other types by its superior denseness among the population of generation representatives. Ecologically Leucozonella mesoleuca is a type of mezocserobiont, and mostly spread in mountains such as Chotkol, Kurama, Pskom, Turkistan and Nurota. Leucozonella mesoleuca wakes up from winter rest (at the early spring season) in the second ten-day of March on the areas of hills, and in mountains the process happens in the beginning of april, then after active nourishment starts preparing to copulation. In the first ten-days of april molluscs will be ready to multiply. The mollusc that is ready to multiply after finding its pair, the three staged mating "game" will get start.